2015
DOI: 10.1158/1541-7786.mcr-15-0020-t
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor NF2 Blocks Cellular Migration by Inhibiting Ectodomain Cleavage of CD44

Abstract: Ectodomain cleavage (shedding) of transmembrane proteins by metalloproteases (MMP) generates numerous essential signaling molecules, but its regulation is not totally understood. CD44, a cleaved transmembrane glycoprotein, exerts both antiproliferative or tumor-promoting functions, but whether proteolysis is required for this is not certain. CD44-mediated contact inhibition and cellular proliferation are regulated by counteracting CD44 C-terminal interacting proteins, the tumor suppressor protein merlin (NF2) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 49 publications
1
34
1
Order By: Relevance
“…Some of our results need further explanation and suggest additional uncovered regulatory components. In one early study CD44 S291A was reported to inhibit cellular migration (65), while we found that it enhances CD44 cleavage, a feature that is required for migration in our hands (4). The reason for this discrepancy has yet to be uncovered.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Some of our results need further explanation and suggest additional uncovered regulatory components. In one early study CD44 S291A was reported to inhibit cellular migration (65), while we found that it enhances CD44 cleavage, a feature that is required for migration in our hands (4). The reason for this discrepancy has yet to be uncovered.…”
Section: Discussioncontrasting
confidence: 64%
“…These data prompted us to examine the role of the ICD modifications in vivo. We already showed that cleavage of CD44 is relevant for cellular migration (4). We next tested the potential physiological role of ICD modification in neuregulin release in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleaved HBEGF binds and activates ERBB4, which signals for cell survival (Hilliard et al, 2011) (Figure 3E). An additional link between CD44v6, proteases and apoptosis resistance relies on CD44v6 ectodomain cleavage by MMP9 and ADAM10 (Kim and Jung, 2012; Hartmann et al, 2015), where CD44-associated MMP14 accounts for proMMP9 cleavage and activation (Tjwa et al, 2008). Finally, CD44-dependend apoptosis resistance can proceed via CD44-promoted MMP9 expression (Desai et al, 2009), high CD44 and MMP9 expression being associated with a poor prognosis in CLL patients (Kivisaari et al, 2010; Buggins et al, 2011).…”
Section: Linking Cd44/cd44v6 Activities To Cic Featuresmentioning
confidence: 99%
“…Thus, only a small proportion (ϳ15%) of CD44 molecules is subject to cleavage (78), whereas the association between ADAMs and neuregulin-1 may approach 100% (77). It is remarkable that in many scores of experiments, the proportion of single-chain TSHR on the cell surface persists in the 30 -50% range (for example, see Ref.…”
Section: Regulation Of the Interaction Between Adams And The Tshrmentioning
confidence: 99%